The Development of the Indonesian Football Industry and its influence Towards National Reputation - Prawira, Andrew; Suhianto, Yuda (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2024)
The Indonesian football industry has undergone significant transformation and growth over the years, making it a noteworthy aspect of the nation's cultural and economic landscape. This paper explores the dynamic development of the Indonesian football industry and its profound influence on the country's national reputation. It delves into the historical roots of football in Indonesia, tracing its evolution from a grassroots movement to a professional and commercialized sport. The analysis covers various facets of the football industry, including club competitions, player development, infrastructure investment, and fan engagement. Moreover, it examines how football has become a powerful soft power tool for Indonesia, enhancing its global image and fostering international diplomatic relations. The study underscores the multifaceted impact of the Indonesian football industry on national identity, pride, and diplomacy, illustrating its role as a pivotal driver of the country's reputation on the global stage. Keywords: Football, Indonesia, Nation, Reputation, Image